Association of adiponectin gene variation with progression of nonalcoholic fatty liver disease: A 4‐year follow‐up survey. Issue 10 (October 2015) - Zhou, Yong Jian; Zhang, Zong Sheng; Nie, Yu Qiang; Cao, Jie; Cao, Chuang Yu; Li, Yu Yuan
Abstract : Objective: To explore the role of tagging single nucleotide polymorphisms ( tag SNPs) in the adiponectin gene in the natural course of nonalcoholic fatty liver disease (NAFLD). Methods: The participants were chosen from our previous survey containing 3543 individuals. Finally, a total of 696 participants who had been followed up for a median of 4 years were included. Each participant was administered with an interview, physical examination, blood tests and ultrasonic examination at both baseline and end‐point. Polymerase chain reaction‐restriction fragment length polymorphism was applied to determine seven tagSNPs in the adiponectin gene, namely, rs182052, rs16861205, rs822396, rs7627128, rs1501299, rs2241767 and rs3774261. Ordinal logistic regression was used to screen risk factors of NAFLD progression as well as the susceptibility to the disease. Haplotypes analyses were performed to confirm the results. Results: After adjusting for age and gender, rs1501299 (G276T), rs2241767 (A45G) and rs3774261 (A712G) were found to be risk factors of both susceptibility (OR 5.040, 7.471 and 3.546, respectively) and progression (OR 3.83, 3.51 and 3.30, respectively) to NAFLD. Nevertheless, rs182052, rs16861205, rs822396 and rs7627128 had no impact on them. These findings were confirmed by haplotype analysis. Conclusion: The tag SNPs rs2241767, rs1501299 and rs3774261 in the adiponectin gene are risk factors for the individuals' susceptibility to and progression of NAFLD.